ECOCRITICAL STUDY ON THE "SENDHANG TIRTA PANGGESANGAN" GEGURITAN - Atik Dina Nasekha; Mulyana Mulyana (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2024)
Geguritan (Javanese poetry) is a fascinating literary work to study from various perspectives, one of which is from the perspective of ecocriticism. Ecocriticism examines environmentally oriented criticism of literary works. This research examines ecocriticism in the geguritan "Sendhang Tirta Panggesangan," created by S. Wignya Raharja. This type of research is qualitative descriptive research. The data in this research is in the form of sentences in the "Sendhang Tirta Panggesangan" geguritan. The data collection technique used was the literature study technique, which involved studying reference sources from similar articles regarding literary ecocriticism. The data analysis technique used is content analysis, which is carefully reading the geguritan and analyzing it using literary ecocriticism. The results of the research show that there is ecocriticism contained in the "Sendhang Tirta Panggesangan" geguritan in the form of a depiction of the sendhang environment, which has been polluted and is no longer natural as a result of human activities.